Intangible Cultural Heritage: Accounting Assessment of Intangible Assets Performing Arts using Postmodern Paradigm - Satria, Hendy; Ibrahim, Andika Noor; Chartady, Rachmad; Marlinda, Charly; Alamsyahbana, Muhammad Isa (Yayasan Keluarga Guru Mandiri, 2026)
UNESCO has been determining the intangible cultural heritage of Indonesia since 2008. The Indonesian government began implementing the same policy at the national level in 2013. To date, 1086 determinations of Indonesia's intangible cultural heritage have been made. This Determination activity is carried out as an effort to protect and preserve Indonesia's intangible culture. This research focuses on the application of accounting for assessing intangible cultural heritage in Indonesia, particularly in Tanjungpinang, Riau Islands. The research method employed in this study is a qualitative, ethnomethodological approach grounded in the postmodernist paradigm. The results of this study indicate that Makyong performing arts still instill seven Malay cultural values, namely, politeness, customs, honesty, tradition, justice, courage, and humility. Based on the accounting assessment of intangible cultural heritage assets, five assessment instruments were identified: allocation value, reconstruction value, formed value, public contribution, and external agent contribution, totaling IDR 164,708,000.